Cardio-Oncoimmunology: Cardiac Toxicity, Cardiovascular Hypersensitivity, and Kounis Syndrome - Nicholas G. Kounis; Ming-Yow Hung; Cesare de Gregorio; Virginia Mplani; Christos Gogos; Stelios F. Assimakopoulos; Panagiotis Plotas; Periklis Dousdampanis; Sophia N. Kouni; Anastasopoulou Maria; Grigorios Tsigkas; Ioanna Koniari (Life, 2024)
Cancer therapy can result in acute cardiac events, such as coronary artery spasm, acute myocardial infarction, thromboembolism, myocarditis, bradycardia, tachyarrhythmias, atrio-ventricular blocks, QT prolongation, torsades de pointes, pericardial effusion, and hypotension, as well as chronic conditions, such as hypertension, and systolic and diastolic left ventricular dysfunction presenting clinically as heart failure or cardiomyopathy. In cardio-oncology, when referring to cardiac toxicity and cardiovascular hypersensitivity, there is a great deal of misunderstanding. When a dose-related cardiovascular side effect continues even after the causative medication is stopped, it is referred to as a cardiotoxicity. A fibrotic response is the ultimate outcome of cardiac toxicity, which is defined as a dose-related cardiovascular adverse impact that lasts even after the causative treatment is stopped. Cardiotoxicity can occur after a single or brief exposure. On the other hand, the term cardiac or cardiovascular hypersensitivity describes an inflammatory reaction that is not dose-dependent, can occur at any point during therapy, even at very low medication dosages, and can present as Kounis syndrome. It may also be accompanied by anti-drug antibodies and tryptase levels. In this comprehensive review, we present the current views on cardiac toxicity and cardiovascular hypersensitivity, together with the reviewed cardiac literature on the chemotherapeutic agents inducing hypersensitivity reactions. Cardiac hypersensitivity seems to be the pathophysiologic basis of coronary artery spasm, acute coronary syndromes such as Kounis syndrome, and myocarditis caused by cancer therapy.